To what extent does renewable energy deployment reduce pollution indicators? the moderating role of research and development expenditure: Evidence from the top three ranked countries - Gharbi, Inés; Kammoun, Aïda; Kefi, Mohamed Karim (Frontiers in Environmental Science, 2023)
Climate change, pollution, drought, and rising seas impede the achievement of the seventh sustainable development goal SDG#7 “affordable and clean energies”. To counter these threats, the use of Renewable Energy (RE) as an alternative to conventional energy plays an important role in sustainable development. In this context, the purpose of our paper is to investigate the effect of Renewable Energy deployment on environmental protection in China, The United States of America (USA), and Germany: the top three ranked countries in terms of REs production, according to RENEWABLE 2021 GLOBAL STATUSREPORT. To achieve this objective, the paper adopts a Panel fully modified OLS (FMOLS) method. Results declare that renewable energy significantly reduce pollution indicators; furthermore, we find that Research and development fully moderate this relationship. The findings of this study emphasize the importance of increasing spending on Research and development activities in the RE sector. In addition, the countries studied and countries around the world should pay greater attention to investment in research and development to support the long-term plan for advancing sustainable energy sources for feasible energy and economic development.